Carcinoma cuniculatum of the mandible: A case report of a less explored entity - Amritha James; Nandhini Gunasekaran; Rameshkumar Annasamy; Rajkumar Krishnan (Oral Oncology Reports)
Oral carcinoma cuniculatum (OCC) is a rare clinicopathological variant of oral squamous cell carcinoma (OSCC) which presents with a unique histopathological pattern. The lesion is infrequently reported in literature due to its rarity. Diagnosis of this lesion is often challenging due to its close histopathological similarity to other verruco-papillary lesions. We report a unique case of OCC within the mandible which clinically presented with signs consistent with chronic osteomyelitis, but on histopathological examination was revealed to be malignant epithelial neoplasia showing characteristic features of OCC.